2015
DOI: 10.1080/13854046.2016.1140228
|View full text |Cite
|
Sign up to set email alerts
|

The American Academy of Clinical Neuropsychology, National Academy of Neuropsychology, and Society for Clinical Neuropsychology (APA Division 40) 2015TCNProfessional Practice and ‘Salary Survey’: Professional Practices, Beliefs, and Incomes of U.S. Neuropsychologists

Abstract: Objective: The current survey updated professional practice and income information pertaining to clinical neuropsychology. Methods: Doctoral-level members of the American Academy of Clinical Neuropsychology, Division 40 (Clinical Neuropsychology) of the American Psychological Association, and the National Academy of Neuropsychology and other neuropsychologists, as well as postdoctoral trainees in the Association of Postdoctoral Programs in Clinical Neuropsychology and at other training sites were invited to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 25 publications
4
67
0
1
Order By: Relevance
“…programs. These results were comparable to the postdoctoral trainees recently surveyed in Sweet et al (2015) and with the proportion of Ph.D. to Psy.D. programs with self-declared neuropsychology training It was not possible to determine the specific response rate to the survey, given that there is no objective listing of all neuropsychology trainees in North America.…”
Section: Participantssupporting
confidence: 93%
See 3 more Smart Citations
“…programs. These results were comparable to the postdoctoral trainees recently surveyed in Sweet et al (2015) and with the proportion of Ph.D. to Psy.D. programs with self-declared neuropsychology training It was not possible to determine the specific response rate to the survey, given that there is no objective listing of all neuropsychology trainees in North America.…”
Section: Participantssupporting
confidence: 93%
“…trainees having more than $200,000 in debt. Most trainees reported the likely starting salary after postdoctoral fellowship to be between $80 and 100,000 annually, which is consistent with the most recent neuropsychology salary survey (Sweet et al, 2015). This financial burden in neuropsychology trainees, given the gap that may occur between debt and salary, has also been discussed extensively within the AACN Community listservs and is a concern as indicated by the 76 posts related to this topic in January 2016 and further posts in April 2016.…”
Section: Student Debtsupporting
confidence: 61%
See 2 more Smart Citations
“…Prior research has demonstrated that up to 40% of children aged four years old already exhibit difficulties with attention to warrant teacher and parent concern (Palfrey, Levine, Walker, & Sullivan, 1985). Moreover, Attention Deficit Hyperactivity Disorder has emerged as one of the most common childhood conditions and one of the top reasons for neuropsychological referral (Sweet, Benson, Nelson, & Moberg, 2015). Given that attention plays a fundamental role in all cognitive, social, and emotional processes, impairments in these skills are associated with poor adaptive functioning, reduced quality of life, and a variety of academic problems (Isquith, Crawford, Espy, & Gioia, 2005;Miller & Hinshaw, 2010).…”
Section: Introductionmentioning
confidence: 99%